Pentingnya Pemeriksaan Jumlah Leukosit Urin dalam Manajemen Diabetes Mellitus: Studi Kasus Rumah Sakit Estomihi Kota Medan - Ritonga, Triana Permatasari; Sartini, Sartini; Rahmiati, Rahmiati; Fauziah, Ida (Universitas Medan Area, 2023)
Diabetes Mellitus is commonly referred to as The Silent Killer because this disease can affect all organs of the body and cause some various symptoms, one of them is in the urinary tract. When the blood glucose levels are high (glucosuria), the excess will be excreted through the urine. In patients with glucosuria, it will cause an increase in urin leukocytes or is called leukocyturia. This research is entitled Analysis of Urin Leukocyte Count of Patients with Diabetes Mellitus at Estomihi Hospital, Medan City. The purpose of this study was to determine the number of urin leukocytes in patients with diabetes mellitus at Estomihi Hospital, Medan City. This study used a descriptive method by means of laboratory examinations to determine the number of urin leukocytes in patients with diabetes mellitus at Estomihi Hospital. The results of study showed that there was an increase in the number of urin leukocytes in patients with diabetes mellitus at Estomihi Hospital. From a total of 30 urin samples from diabetes mellitus patients, 12 people (40%) had normal urine leukocyte counts, and 18 people (60%) suffered from leukocyturia. The results of observations based on gender for female patients detected greater leukocyturia in the amount of 66.7%. Based on the results of the analysis of Personal hygiene effect on the incidence of leukocyturia in patients with diabetes mellitus at Estomihi Hospital, Medan City.